2018
DOI: 10.1097/md.0000000000012626
|View full text |Cite
|
Sign up to set email alerts
|

Blood homocysteine levels could predict major adverse cardiac events in patients with acute coronary syndrome

Abstract: The Global Registry of Acute Coronary Events (GRACE) risk score independently predicts major adverse cardiac events (MACEs) in patients with acute coronary syndrome (ACS). This study aims to evaluate whether the level of plasma homocysteine in addition to the GRACE score enhances the predictive value for MACEs in patients with acute coronary syndrome.A total of 361 patients with ACS evaluated at our hospital were included in the study and tested for blood homocysteine levels. We recorded 40 (11.1%) instances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(30 reference statements)
1
14
1
2
Order By: Relevance
“…Other demographic and clinical factors such as diet habits, physical activity, drug treatment, chronic inflammation or the methods of measuring Hcy may also be implicated in the these inconsistent results. Interestingly, we found that Hcy was negatively associated with BMI in schizophrenia, which was inconsistent with most of previous studies showing that high Hcy may be related to obesity and increase the risk of coronary heart disease 33 , 34 . This may be attributed to the effects of different diseases, different stages of disease development 18 , or medication treatment regiments 35 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other demographic and clinical factors such as diet habits, physical activity, drug treatment, chronic inflammation or the methods of measuring Hcy may also be implicated in the these inconsistent results. Interestingly, we found that Hcy was negatively associated with BMI in schizophrenia, which was inconsistent with most of previous studies showing that high Hcy may be related to obesity and increase the risk of coronary heart disease 33 , 34 . This may be attributed to the effects of different diseases, different stages of disease development 18 , or medication treatment regiments 35 .…”
Section: Discussioncontrasting
confidence: 99%
“…Correlation analysis showed that HCY levels were negatively associated with BMI. www.nature.com/scientificreports/ disease 33,34 . This may be attributed to the effects of different diseases, different stages of disease development 18 , or medication treatment regiments 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Some developed and developing countries, including China, the United States and Japan have large and rapidly aging populations. Hcy is an important diagnostic marker for cerebral infarction (15); therefore, it is of great importance to develop an effective Hcy detection method with potentially beneficial values in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in plasma Hcy levels are often multifactorial, with genetic and acquired components [ 54 ]. While the correlation between hyperhomocysteinemia and vascular disease is well established [ 55 57 ], the underlying mechanisms are under investigation. Animal and cell models have highlighted the potential mechanisms for Hcy-mediated damage to the vascular architecture, but evidence of a causal relationship between hyperhomocysteinemia and vascular disease in humans remains to be shown [ 58 ].…”
Section: Pathogenesis Of Hyperhomocysteinemia and Its Role As A Risk mentioning
confidence: 99%